THU0008 Mast cells show a reprogrammed transcriptional signature following repeated igg stimulations. (15th June 2017) - Messemaker, T; Suurmond, J; Habets, K; Heijink, M; Schonkeren, J; Dorjee, A; Giera, M; Huizinga, T; Toes, R; Kurreeman, F
Abstract : Background: Mast cell numbers are increased in the rheumatoid arthritis joint. We have previously shown that mast cells can be activated by IgG-ACPA leading to the production of proinflammatory cytokines. However, not much is known about the resulting function when mast cells would repeatedly engage IgG, a likely scenario given the long life span of mast cells (up to a year) and the perpetual presence of IgG-ACPA in the joints. We have recently shown that mast cells triggered repeatedly through their Ig Fc epsilon receptor undergo a reprogramming of their responses ( Suurmond et al. JACI, 2016 by expressing de-novo transcribed genes in the antigen presentation and pathogen defence response pathways. Objectives: The aim of the current work was to determine whether mast cells show similar changes in their response mode following repeated interactions with IgG. Methods: Human cord blood-derived mast cells were treated for 2 weeks with plate-bound IgG. The expression profile of naive or treated mast cells was measured through RNA sequencing, quantitative RT-PCR, flow cytometry. Protein secretion was measured with ELISA and Luminex assays. Metabolic changes were measured using HPLC mass-spectrometry. Results: Similar to our previous work on Fc Epsilon receptor, we observe a dampening of the normal IgG responses with a set of novel genes upregulated. Interestingly, de-novo expressed genes consisted of DHCR7 and DHCR24, key enzymes in the cholesterol pathway. Pathway analysis confirms an enrichment of genes in this pathway following repeated IgG triggering. Preliminary data on metabolic profiling reveals a decrease in phospholipid levels in repeatedly activated mast cells. Conclusions: Our study provides evidence that mast cells are reprogrammed upon repeated IgG triggering. In contrast to repeated Fc Epsilon Receptor triggering, different pathways are affected, implying stimulus-specific effects. Our work has important implications for the understanding the role of mast cells in rheumatoid arthritis. Disclosure of Interest: None declared